2015
DOI: 10.1007/s00709-015-0906-2
|View full text |Cite|
|
Sign up to set email alerts
|

Drought tolerance and proteomics studies of transgenic wheat containing the maize C4 phosphoenolpyruvate carboxylase (PEPC) gene

Abstract: Enhancing drought tolerance of crops has been a great challenge in crop improvement. Here, we report the maize phosphoenolpyruvate carboxylase (PEPC) gene was able to confer drought tolerance and increase grain yield in transgenic wheat (Triticum aestivum L.) plants. The improved of drought tolerance was associated with higher levels of proline, soluble sugar, soluble protein, and higher water use efficiency. The transgenic wheat plants had also a more extensive root system as well as increased photosynthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…This is in agreement with previous studies where it was shown that abiotic stresses can induce PEPC gene expression in wheat, A. thaliana , and sorghum (Echevarría et al , 2001; González et al , 2003; García-Mauriño et al , 2003; Sánchez et al , 2006). Moreover, recent studies demonstrated that the maize PEPC gene was able to confer drought tolerance and increase grain yield in transgenic wheat plants (Qin et al , 2016). Furthermore, in agreement with an earlier report on drought (Lawlor and Tezara, 2009), our data showed that photosynthesis-related proteins, such as PHOTOSYSTEM II SUBUNIT Q and PHOTOSYSTEM II SUBUNIT P, were down-regulated upon mannitol-induced stress, as were many chloroplast-located proteins.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with previous studies where it was shown that abiotic stresses can induce PEPC gene expression in wheat, A. thaliana , and sorghum (Echevarría et al , 2001; González et al , 2003; García-Mauriño et al , 2003; Sánchez et al , 2006). Moreover, recent studies demonstrated that the maize PEPC gene was able to confer drought tolerance and increase grain yield in transgenic wheat plants (Qin et al , 2016). Furthermore, in agreement with an earlier report on drought (Lawlor and Tezara, 2009), our data showed that photosynthesis-related proteins, such as PHOTOSYSTEM II SUBUNIT Q and PHOTOSYSTEM II SUBUNIT P, were down-regulated upon mannitol-induced stress, as were many chloroplast-located proteins.…”
Section: Discussionmentioning
confidence: 99%
“…PEPC is a multifaceted key enzyme that in C 3 plants is linked to the provision of Krebs cycle intermediates, and its overexpression in transgenic wheat improved drought tolerance and grain yield (Qin et al, 2015). PEPC expression has not been widely studied during early growth in durum wheat plants.…”
Section: Discussionmentioning
confidence: 99%
“…For example, an up-regulated PEPC expression in response to salinity or drought stress has been well documented in C 3 , C 4 and CAM plants678910. Meanwhile, overexpression of PEPC gene in transgenic plants enhanced their tolerance to drought or salt stress11, whereas knockdown of PEPC leading to increased sensitivity to osmotic stress12.…”
mentioning
confidence: 99%